1% Tirbanibulin Ointment for Actinic Keratoses on Upper Extremities: A Retrospective Case Review Study - Álvaro Iglesias-Puzas; Alberto Conde-Taboada; Lucía Campos-Muñoz; Ana Sirgado-Martínez; Eduardo López-Bran (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)